Suicidal Ideation in Adolescence: A Perspective View on the Role of the Ventromedial Prefrontal Cortex - Morese, Rosalba; Longobardi, Claudio (Frontiers in Psychology, 2020)
Suicide in adolescence is a worldwide issue, and it continues to present a serious problem in terms of its prevention. Among the various aspects of suicide, a very interesting area of research is represented by suicidal ideation. Recently, neuroimaging-based methods have made it possible to study the cognitive processes involved in several social situations and clinical conditions. This theoretical perspective article with an interdisciplinary approach integrates evidence from developmental psychology and social neuroscience with the aim of investigating the role of the brain area responsible for regulating negative emotions during the cognitive processes of suicidal ideation: the ventromedial prefrontal cortex. By highlighting the role of brain areas in the few studies published so far, it is possible to develop perspectives of considerable impact. Studying and understanding the role of brain areas involved in suicidal thoughts in adolescents could facilitate the creation of new perspectives on prevention programs and interventions.